1995
DOI: 10.1002/1097-0142(19950315)75:6+<1497::aid-cncr2820751519>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing growth rate of recurrent stomach cancers as determined by analysis of serum carcinoembryonic antigen

Abstract: Background. Although there are many reports regarding the growth rate of human tumors, those discussing stomach cancer are rare due to the difficulty in evaluating the growth rate of stomach cancer. Stomach cancers grow with either a large central depression or through severe invasion. Metastatic sites of stomach cancer, however, grow expandingly, as with pulmonary tumors. Methods. The reported doubling time estimate, based on the serum level of carcinoembryonic antigen (CEA), agreed with the actual tumor doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…There is a large degree of variation of TDT between tumors of different tissue origins. Pituitary adenoma, for example, has an extremely long DT of 506-5378 days [133] while stomach cancer may have a minimal DT of as little as 12 days [137].…”
Section: Tumor Doubling Time (Tdt)mentioning
confidence: 99%
“…There is a large degree of variation of TDT between tumors of different tissue origins. Pituitary adenoma, for example, has an extremely long DT of 506-5378 days [133] while stomach cancer may have a minimal DT of as little as 12 days [137].…”
Section: Tumor Doubling Time (Tdt)mentioning
confidence: 99%
“…This antigen was subsequently labelled as carcinoembryonic antigen (CEA). This is [13] has found that CEA doubling time in gastric cancers ranged from 12 to 105 days with median of 32 days. However, this was found to be significantly shorter in papillary adenocarcinoma of stomach.…”
Section: Resultsmentioning
confidence: 91%
“…Concerning tumor marker doubling time, Staab et al [22] reported the CEA doubling time in colon cancer. Moreover, Takahashi et al [23] reported a significant correlation between the CEA doubling time and postoperative survival time among patients with stomach cancer who did not receive chemotherapy. Prostate specific antigen doubling time was reported to be a strong prognostic factor in patients with prostate cancer [24].…”
Section: Discussionmentioning
confidence: 99%